Kursus Calon Pengantin Perspektif Maslahah Mursalah (Studi Terhadap Pandangan Masyarakat Kabupaten Kaur) - Irlianuddin, Irlianuddin (UIN Fatmawati Sukarno Bengkulu, 2021)
Abstract: This research was conducted at the KUA in Kaur Regency by raising the issue of how the implementation of the prospective bride and groom course was carried out by the KUA, and how successful the implementation of the prospective bride and groom course was in minimizing the divorce rate in Kaur Regency and how the people of Kaur Regency viewed the implementation of the prospective bride and groom course. as a condition of marriage in the perspective of maslahah mursalah. To answer these problems, the research used juridical empirical, with a law approach, and a conceptual approach. The data were obtained through observations and interviews with the head of KUA, Suscatin participants and the community, then after the data was obtained, the material was reconstructed and analyzed qualitatively by using deductive and inductive methods. The results of the study show that 1) The implementation of the prospective bride and groom course conducted by the KUA in Kaur Regency is still not in accordance with the laws and regulations governing suscatin, namely the Regulation of the Director General of Islamic Community Guidance, Ministry of Religion Number DJ.II/491 of 2009. 2) The success of the implementation of the substitute candidate courses in North Kaur KUA, Muara Sahung KUA and Padang Guci Ulu KUA, is starting to be seen and felt by the community even though it is not optimal. 3) The views of the people of Kaur Regency in the implementation of the prospective bride and groom course as a condition of marriage in the perspective of maslahah mursalah there are two (2) views. First, they agree with the bride and groom course as a condition of marriage, Second, they do not agree with the prospective bride course as a condition of marriage. Keywords: Bride and Groom Course, Divorce and Maslahah Mursalah Abstrak: Penelitian ini diadakan di KUA yang ada di Kabupaten Kaur dengan mengangkat permasalahan bagaimana pelaksanaan kursus calon pengantin yang dilakukan oleh KUA, dan sejauhmana keberhasilan pelaksanaan kursus calon pengantin dalam meminimalisir angka perceraian di Kabupaten Kaur serta bagaimana masyarakat Kabupaten Kaur memandang dalam pelaksanaan kursus calon pengantin sebagai syarat pernikahan dalam perspektif maslahah mursalah. Untuk menjawab permasalahan tersebut, penelitian yang digunakan yuridis empiris, dengan pendekatan Undang-Undang, dan pendekatan konseptual. Data didapat melalui pengamatan dan wawancara kepada kepala KUA, peserta Suscatin dan masyarakat, kemudian setelah data didapat dilakukan rekotruksi bahan dengan dianalisis secara yuridis kualitatif dengan metode deduktif dan induktif. Dari hasil penelitian menunjukan bahwa 1) Pelaksanaan kursus calon pengantin yang dilakukan oleh KUA di Kabupaten Kaur masih belum sesuai dengan Peraturan perundang undangan yang mengatur tentang suscatin, yaitu Peraturan Direktur Jendral Bimbingan Masyarakat Islam Departemen Agama Nomor DJ.II/491 Tahun 2009. 2) Keberhasilan pelaksanaan kursus calon penganti yang ada di KUA Kaur Utara, KUA Muara Sahung dan KUA Padang Guci Ulu, mulai terlihat dan dirasakan oleh masyarakatnya walaupun belum maksimal. 3) Pandangan masyarakat Kabupaten Kaur dalam pelaksanaan kursus calon pengantin sebagai syarat pernikahan dalam perspektif maslahah mursalah ada dua (2) pandangan Pertama, setuju dengan adanya kursus calon pengantin sebagai syarat perkawinan, Kedua, tidak setuju dengan kursus calon pengantin sebagai syarat perkawinan. Kata Kunci: Kursus Calon Pengantin, Perceraian dan Maslahah Mursalah